FACTORS LIMITING THE EFFECTIVE USE OF INNOVATIVE SCIENCE TEACHING STRATEGIES IN SENIOR SECONDARY SCHOOLS IN SOUTH WEST, NIGERIA: - Olufunke Olayinka KAYODE; Abdulraheem Dare GBIGBADUA; Hafees Tosin SULYMAN (CV. RADJA PUBLIKA, 2024)
Using a descriptive survey research design, this study examined and discussed the problems associated with implementing a few chosen innovative twenty scientific teaching practices. All senior high school science instructors in a few chosen states in the southwest of Nigeria made up the study population. A purposively random sample of 622 science teachers drawn from Ekiti, Osun, Oyo and Lagos States were involved in the study. A researcher designed survey questionnaire with reliability coefficient of 0.91 was used to collect data from the teacher respondents. For the purpose of answering the study's research question, frequency counts and percentages were used to analyse the data. Findings of the study revealed the following factors as limiting the effective use of innovative teaching strategies: non-availability of teaching resources, strategies being demanding and stressful, poor motivation for teachers, absence of in-service training for teachers, and students non-commitment to extra effort in science learning. Finally, appropriate recommendations were proffered to enhance the use of innovative strategies in science teaching.